Molecules and mechanisms controlling the active DNA demethylation of the mammalian zygotic genome. Issue 11 (26th August 2014) - Ma, Jun-Yu; Zhang, Teng; Shen, Wei; Schatten, Heide; Sun, Qing Yuan
Abstract: The active DNA demethylation in early embryos is essential for subsequent development. Although the zygotic genome is globally demethylated, the DNA methylation of imprinted regions, part of repeat sequences and some gamete-specific regions are maintained. Recent evidence has shown that multiple proteins and biological pathways participate in the regulation of active DNA demethylation, such as TET proteins, DNA repair pathways and DNA methyltransferases. Here we review the recent understanding regarding proteins associated with active DNA demethylation and the regulatory networks controlling the active DNA demethylation in early embryos.